Sunday

April 20, 2014

April 20, 2014

Posted by **ANGEL** on Wednesday, June 12, 2013 at 12:25pm.

How to do this ?

- Math -
**Ms. Sue**, Wednesday, June 12, 2013 at 12:41pm4x+ (x+2)= 9x-10

5x + 2 = 9x - 10

2 + 10 = 9x - 5x

12 = 4x

12/4 = x

3 = x

**Related Questions**

calculus - f(x)=(9x^2–8)^6(4x^2–5)^11 Find f'(x) I got (9x^2-8)^6 *11(4x^2-3)^...

Calculus-help please - f(x)=(9x^2–8)^6(4x^2–5)^11 What's f'(x)= i found (9x^2-8...

algebra,math - My qustion is for the following the problem reads as follows (x-1...

math - Simplify the Expressions 1) -4(3x-3) + 9(x+1)= -3x21 2) -9x(5x+4)+10(x+3...

Maths - is this correct... (3x^2+4x-3)^2-(3x^2-x+2)^2 then is it this (9x^4+24x^...

Math - Find the horizontal asymptote, if any, of the graph of the given function...

Math - Find the horizontal asymptote, if any, of the graph of the given function...

Math/Algebra - Could you also check these to. Thanks. (4x^2 + 9x - 1) - (5 - x^2...

11th grade algebra 2 - (1-7) write each function in vertex form (8-10) write ...

Algebra 2 - (1-7) write each function in vertex form (8-10) write each funtion ...